Оптимізація передачі якості голосу та ємності мережі GSM методами штучного інтелекту - Міхняк , Софія Іванівна (Національний університет «Львівська політехніка», 2022)
Бакалаврська кваліфікаційна робота виконана студенткою групи КН-409 Міхняк Софією Іванівною. Тема «Оптимізація передачі якості голосу та ємності мережі GSM методами штучного інтелекту». Робота направлена на здобуття ступеня бакалавр за спеціальністю 122 «Комп’ютерні науки». Результати виконання описані на 47-ми сторінках, з 3-ма таблицями, 17-ма рисунками, 2-ма діаграмами та одним додатком з посиланням на репозиторій з кодом побудованої системи та на записник Colab, у якому проводились дослідження. Всього є 15 посилань на відкриті джерела. Метою дипломної роботи є створення та розробка програмного продукту, що автоматизує процес налаштування параметрів FR використання для мережі GSM. Об’єктом дослідження є автоматизована система вибору параметрів, що відповідають за якість передачі голосу. В результаті виконання дипломної роботи було розроблено програмний продукт, який покращує якість передачі голосу. Автоматизована система представлена агентом навчання з підкріпленням, який визначає як оптимізувати порогові значення для FR. Degree work executed by the student of group CS-409 Mikhniak Sofiia Ivanivna. The topic is 'Optimization of voice quality transmission and capacity of GSM network by artificial intelligence methods'. Work is directed on reception to obtain a bachelor's degree in a specialty 122 «Computer Science». Result present on 47 pages, with 3 tables, 17 pictures, 2 diagrams and 1 addition with links to GitHub repository with code for system and Colab notebook with experiments. Overall there are 15 links to open sources. Mobile networking is now an integral part of our lives, and improving service and optimizing resource usage is crucial. GSM supports full-rate calls and half-rate calls. A full-rate (FR) call uses one-time slot in every frame, while a half-rate (HR) call uses one-time slot in every two frames. Once a mobile station initiates a full-rate (half-rate) call request, the mobile station will operate in full-rate (half-rate) mode until the call is terminated. If during the call attempt, the nearest base station will not have free channels - blocking occurs. It is needed to find a trade-off between FR and HR usage. The solution depends on the amount of available TCH channels and traffic. To regularize the FR usage are used two parameters - upper and lower limit. These parameters control adaptive multi-rate (AMR) TCH channel rate determination on the base station controller level accordingly to the cell load in traffic channel allocation. The upper limit defines the upper percentage of free full rate resources. AMR full rate TCHs are allocated when the number of free full rate resources exceeds the values of the parameter. Respectively the lower limit defines the lower percentage of free full rate resources. AMR full rate TCHs are allocated until the number of free full rate resources is reduced below the value of the parameter. AMR half rate resources are then allocated. If the lower limit is higher than upper limit, then the effect of these two base station controller level channel rate control parameters deactivate.
Optimization of voice quality transmission and capacity of GSM network by artificial intelligence methods
Keywords: автоматизована система, GSM, часові ряди, навчання з підкріпленням, automated system, GSM, time series, reinforcement learning.